Status of Food Processing Industries in India (International Journal of Food and Nutritional Sciences, 2022)
A well-developed food processing sector with higher level of processing helps in the reduction of wastage, improves value addition, promotes crop diversification, ensures better return to the farmers, promotes employment as well as increases export earnings. This sector is also capable of addressing critical issues of food security, food inflation and providing wholesome, nutritious food to the masses. Over the years agricultural production in India has consistently recorded higher output. India ranks third in the world in the production of Milk, Ghee, Pulses, Ginger, Banana, Guava, Papaya and Mango. Further, India ranks second in the world in the production of Rice, Wheat and many other fruits & vegetables. An abundant supply of raw materials, increase in demand for food products and incentives offered by the Government has impacted food processing sector positively.